Landnutzungswandel im Nordjemen seit 1970.: Von der autarken Stammesgesellschaft zum marktwirtschaftlich orientierten Nationalstaat - Kopp, Horst (ERDKUNDE, 1990)
Northern Yemen up to 1970 had been marked by a sedentary, rural tribal population, who aimed at political autonomy through economic autarky. The inability of the system to take up innovations had led to a remarkable adaptation of the land use to the ecological system. Since 1970 the change in land use has been subject to a number of factors which, taken together, initiated the transition to a market orientated production. The capitalization of agriculture, which quickly took place, led to a new assessment of the agrarian locational factors with serious effects on the ecological system, the spatial-structural and the agrarian-social conditions. The development of the infrastructure serves as an indication of the extent of the changes.